1993
DOI: 10.1042/bj2960759
|View full text |Cite
|
Sign up to set email alerts
|

A calmodulin-stimulated Ca2+ pump in plasma-membrane vesicles from Trypanosoma brucei; selective inhibition by pentamidine

Abstract: Despite previous reports [McLaughlin (1985) Mol. Biochem. Parasitol. 15, 189-201; Ghosh, Ray, Sarkar and Bhaduri (1990) J. Biol. Chem. 265, 11345-11351; Mazumder, Mukherjee, Ghosh, Ray and Bhaduri (1992) J. Biol. Chem. 267, 18440-18446] that the plasma membrane of different trypanosomatids only contains Ca(2+)-ATPase that does not show any demonstrable dependence on Mg2+, a high-affinity (Ca(2+)-Mg2+)-ATPase was demonstrated in the plasma membrane of Trypanosoma brucei. The enzyme became saturated with micromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…Although acidocalcisome numbers declined more markedly as compared with the changes in acidocalcisome PP i and polyP, this discordance can be explained by the differences in cell volume of the remaining acidocalcisomes. These phenotypic changes did not lead to significant changes in intracellular Ca 2ϩ levels, in agreement with the reported major role of the plasma membrane in the regulation of intracellular Ca 2ϩ concentration under steady state conditions (65,66). Loss of polyP is in agreement with the presence in acidocalcisomes of the vacuolar transporter chaperone complex (31), which is involved in its synthesis.…”
Section: Tet(؊)supporting
confidence: 74%
“…Although acidocalcisome numbers declined more markedly as compared with the changes in acidocalcisome PP i and polyP, this discordance can be explained by the differences in cell volume of the remaining acidocalcisomes. These phenotypic changes did not lead to significant changes in intracellular Ca 2ϩ levels, in agreement with the reported major role of the plasma membrane in the regulation of intracellular Ca 2ϩ concentration under steady state conditions (65,66). Loss of polyP is in agreement with the presence in acidocalcisomes of the vacuolar transporter chaperone complex (31), which is involved in its synthesis.…”
Section: Tet(؊)supporting
confidence: 74%
“…This characteristic places the enzymes in a novel category together with the acidocalcisomal Ca 2ϩ -ATPase described in T. cruzi (5), D. discoideum (4,8), and T. gondii (6), and the vacuolar Ca 2ϩ -ATPases of S. cerevisiae (3), and E. histolytica (7). The previous detection of a calmodulin-stimulated Ca 2ϩ pump in plasma membrane vesicles from T. brucei bloodstream forms (16) suggests that calmodulin regulates TbPMC2 activity by interacting with as yet unidentified sequences on the enzyme, or that another Ca 2ϩ pump is present in the plasma membrane. Since calmodulininteracting proteins cannot be identified by simple bioinformatic analyses, as their calmodulin-binding domains do not share a common sequence motif (46), further biochemical work with the separate enzymes expressed in yeast could solve this discrepancy.…”
Section: Co-localization Of T Brucei Ca 2ϩ -Atpases With the V-h ϩ -mentioning
confidence: 99%
“…The relative importance of this protein, however, has not been determined nor has it been demonstrated that this protein functions as a Ca 2ϩ pump. A more recent report (16) showed the presence of a calmodulin-stimulated Ca 2ϩ pump in plasma membrane vesicles from T. brucei bloodstream forms. It is evident that a more thorough molecular characterization of the Ca 2ϩ -ATPases present in T. brucei will be essential for structure-function analysis and further development of potential chemotherapeutic agents.…”
mentioning
confidence: 99%
“…Conversely, prolonged exposure to elevated [Ca 2ϩ ] cyt can result in cell death (1,2). Trypanosome survival therefore depends upon redundant energy-dependent processes that carefully control cytosolic free Ca 2ϩ concentrations ([Ca 2ϩ ] cyt ) 1 (3)(4)(5)(6)(7)(8). The present study examines within intact trypanosomes the relative importance of several Ca 2ϩ -transporting organelles.…”
mentioning
confidence: 99%